2020
DOI: 10.1002/aqc.3320
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing tourism benefits associated with top‐predator conservation in coastal British Columbia

Abstract: Facing public concern over costs related to top‐predator reintroductions and conservation, ecosystem services such as ecotourism are often used to evoke benefits that outweigh or offset those costs. Quantifying these benefits using rigorous scientific methods can provide confidence to policymakers and other stakeholders that predators can in fact deliver positive outcomes to people living alongside them. The evaluation of these benefits is often anecdotal or qualitative, however, and empirical quantifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…This study aimed to construct (Figure 4) a whale-dolphin impact mitigation program established on the concepts of operations management, carrying capacity and LAC, and sustainable financing while prior research (Bach and Burton, 2017;Lee et al, 2019b;Martone et al, 2020;Schwarzmann et al, 2021) has investigated domestic tourists' preference heterogeneity, we take an alternative approach to exploring the preferences of tourists with regard to establishing an impact mitigation program for sustainable whale-dolphin tourism. Our results contribute to the extant literature by improving on previous studies that have neglected to draw comparisons between domestic and international tourists across different attributes, such as time schedule management, vessel slowdown distance, maximum boat number, operational guidance, and a conservation fund.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to construct (Figure 4) a whale-dolphin impact mitigation program established on the concepts of operations management, carrying capacity and LAC, and sustainable financing while prior research (Bach and Burton, 2017;Lee et al, 2019b;Martone et al, 2020;Schwarzmann et al, 2021) has investigated domestic tourists' preference heterogeneity, we take an alternative approach to exploring the preferences of tourists with regard to establishing an impact mitigation program for sustainable whale-dolphin tourism. Our results contribute to the extant literature by improving on previous studies that have neglected to draw comparisons between domestic and international tourists across different attributes, such as time schedule management, vessel slowdown distance, maximum boat number, operational guidance, and a conservation fund.…”
Section: Discussionmentioning
confidence: 99%
“…The results also highlighted that unlike Australians, tourists from New Zealand and Europe were less likely to support the feeding of dolphins. In a study by Martone et al (2020), the tourists reported they were willing to pay CA$302 for a higher chance of viewing whales, compared to having a chance to view otters. This preference was a powerful predictor for tourists' choice of wildlife-viewing tour packages on the West Coast of Vancouver Island, in British Columbia, Canada.…”
Section: Choice Experiments Design For the Impact Mitigation Of Swwt ...mentioning
confidence: 99%
“…Understanding changes in coastal ecosystem dynamics resulting from the extinction of the sea cow is particularly important given the role of kelp forests in supporting economically and culturally valuable species. Kelp forests contribute to a variety of ecosystem services such as food provisioning (Markel, 2011) and carbon sequestration (Wilmers et al., 2012) amongst several others (Filbee‐Dexter & Wernberg, 2018; Gregr et al., 2020; Martone et al., 2020; Smale et al., 2013). The diminished ecosystem function in the absence of sea cows has almost certainly reduced the production of these ecosystem services.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no correlation found in the short answers between people agreeing that it would be good to have lynx (or any species), and that predation of deer would be a benefit to reintroductions, this was given as a large reason as to why it would be good to have lynx, as well as being given as a reason for wolves, and as a general benefit to any of these reintroduced species. As Martone et al [37] discovered, the idea of increased ecotourism from these reintroductions was also given as a benefit of reintroductions. Although not largely represented in this study, there was still the mention of 'ecotourism' and 'engaging the public in conservation' as benefits of the reintroductions.…”
Section: Changing Views On Rewildingmentioning
confidence: 99%